Designed ferritin nanocages displaying trimeric TRAIL and tumor-targeting peptides confer superior anti-tumor efficacy - Yoo, Jae Do; Bae, Sang Mun; Seo, Junyoung; Jeon, In Seon; Vadevoo, Sri Murugan Poongkavithai; Kim, Sang-Yeob; Kim, In-San; Lee, Byungheon; Kim, Soyoun (Nature Publishing Group, 2020)
TRAIL is considered a promising target for cancer therapy because it mediates activation of the extrinsic apoptosis pathway in a tumor-specific manner by binding to and trimerizing its functional receptors, DR4 or DR5. Although recombinant human TRAIL has shown high potency and specificity for killing cancer cells in preclinical studies, it has failed in multiple clinical trials for several reasons, including a very short half-life mainly caused by instability of the monomeric form of TRAIL and rapid renal clearance of the off-targeted TRAIL. To overcome such obstacles, we developed a TRAIL-active trimer nanocage (TRAIL-ATNC) that presents the TRAIL ligand in its trimer-like conformation by connecting it to a triple helix sequence that links to the threefold axis of the ferritin nanocage. We also ligated the tumor-targeting peptide, IL4rP, to TRAIL-ATNC to enhance tumor targeting. The developed TRAIL-ATNC(IL4rP) showed enhanced agonistic activity compared with monomeric TRAIL. The in vivo serum half-life of TRAIL-ATNC(IL4rP) was similar to 16-times longer than that of native TRAIL. As a consequence of these properties, TRAIL-ATNC(IL4rP) exhibited efficacy as an anti-tumor agent in vivo against xenograft breast cancer as well as orthotopic pancreatic cancer models, highlighting the promise of this system for development as novel therapeutics against cancer.